Efficiency of activated charcoal powder in stain removal and effect on surface roughness compared to whitening toothpaste in resin composite: In vitro study - Raneem S. Alofi; Haya A. Alsuayri; Lojain S. Mohey; Adeem S. Alofi (Saudi Dental Journal)
Objectives: To evaluate the efficacy of activated charcoal powder on extrinsic stain removal and its effect on surface roughness in stained resin composite in comparison with whitening toothpaste. Materials and methods: Sixty-six disk-shaped composite specimens were fabricated using a custom-made ring mold. The specimens were stained using a coffee solution and stored in distilled water at 37 °C. The specimens were divided randomly into two groups, Group 1: Thirty-Three disks were subjected to brushing using whitening toothpaste (Control), and Group 2: Thirty-Three disks were subjected to brushing using charcoal powder. Specimens were evaluated for surface color and surface roughness at baseline after staining protocol and after the brushing process. Results: Changes in color and surface roughness were highly significant (p < 0.0001) after brushing with activated charcoal powder and whitening toothpaste. However, no significant differences were found in color (p = 0.90) and surface roughness (p = 0.33) between the two bleaching techniques. Conclusion: The changes in the color and surface roughness of resin composite was significant after brushing with activated charcoal powder and whitening toothpaste. However, there were no significant differences between the two techniques.